Atividade docente: os sentidos e significados que uma professora atribui à aquisição da escrita - Rosário, Elaine de Holanda (2012)
This research aims to analyze the experience in teaching between senses and significations that an elementary school teacher gaveto the acquirement of writing by analyzing how is the configuration of the development of the real activity and the real of activity. The data collection of this study was made into a public school of the city of Maceió, in the school year of 2010, in an elementary second-year school class. The theoretical basis of this research was the Sociohistorical Psychology, Clinical Activity and acquirement of writing. Narrative interviews of life history, semi structured and centralized interviews, observations and filming sessions and simple self-confrontation were the procedures and methodological techniques applied. The result of the research finds out the teacher considers the experience in teaching as a profession that the professional has to love as a vocation. Also, the teacher considers the profession painful and easy to perform for women and said that sometimes is difficult to accomplish the work activity.She believed that the teacher function is preparing the students to live in society by demanding their rights and that in the 21th century is indispensable for the students to know how to write. Moreover, she said that the writing learning walks side by side with the writing.